2019
DOI: 10.3390/geosciences9030108
|View full text |Cite
|
Sign up to set email alerts
|

An Instrumented Flume for Infiltration Process Modeling, Landslide Triggering and Propagation

Abstract: Rainfall is the most common cause of landslides, so it is important to know the processes underlying failure starting with the rainfall infiltration processes into the granular soils, the distribution of the water content and pore pressure in both saturated and unsaturated layers, to include their effects in terms of slope stability. Although the literature is full of simulation models, the complexity of phenomena would impose a more detailed analysis by a well-equipped flume. For that purpose, a meter-scale l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The stratigraphy observed on site is shown in Figure 2, and the physical properties (specific gravity G, porosity n, saturated hydraulic conductivity k sat , effective cohesion c and friction angle φ ) are indicated in Table 1. For more details on physical, size distribution and other properties, it is possible to refer to [29,30].…”
Section: Experimental Site and Soil Data Collectionmentioning
confidence: 99%
“…The stratigraphy observed on site is shown in Figure 2, and the physical properties (specific gravity G, porosity n, saturated hydraulic conductivity k sat , effective cohesion c and friction angle φ ) are indicated in Table 1. For more details on physical, size distribution and other properties, it is possible to refer to [29,30].…”
Section: Experimental Site and Soil Data Collectionmentioning
confidence: 99%
“…Tey concluded that the diference of generation mechanism of PWP values may be the deciding factor in the diference in the type of failure. An instrumented fume of a homogeneous slope of pyroclastic soil was analysed by Spolverino et al [25]. Te test showed that the role of suction and soil density was essential for this type of soil and that failure occurred when the suction was close to zero, reducing the efects of apparent cohesion, while density strongly conditioned the dynamics with which the instability manifested itself.…”
Section: Introductionmentioning
confidence: 99%
“…Hydraulic disciplines such as seepage analysis and soil water circulation processes play a decisive role in understanding the processes that cause rain‐induced subsidence. (Bogaard & Greco, 2016; Capparelli et al, 2020; de Luca & Capparelli, 2022; Spolverino et al, 2019; von Ruette et al, 2014; Wieczorek & Glade, 2005). The hydrogeological response of the groundwater regime to the triggering of deep‐seated landslides is strongly correlated to the history of prior rainfall (Lv et al, 2019; Padilla et al, 2014).…”
Section: Introductionmentioning
confidence: 99%